Bosnia and Herzegovina : Public Expenditure and Financial Accountability Assessment - World Bank (Washington, DC, 2014)
The fiscal system in Bosnia and Herzegovina (BiH) is highly decentralized, reflecting the provisions of the country s constitution. The general government sector consists of four relatively autonomous units: BiH Institutions, Brcko District (DB), and two Entities, Federation Bosnia and Herzegovina (FBiH) and Republican Srpska (RS). BiH Institutions are at the central government level (governed by the BiH Council of Ministers); and each Entity has its own government, extra-budgetary funds (EBFs), and local self-governance units. The structure in FBiH has 10 cantons that serve as a middle level of government between the government of FBiH and local self-governance units, and each canton has its own government and some EBFs. Cantons were not covered by this Report, but could be covered later as a sub-national PEFA assessment. A Fiscal Council was created in 2008, with the objective to coordinate fiscal policies for the sake of common interest of BH Institutions, Entities and Brcko District. For the most important role of fiscal coordination, preparing the Global Framework of the Fiscal Balance and Policy, in practice the Fiscal Council decides on revenues from indirect taxation and the budget of BiH Institutions, thereby creating preconditions for budget planning at lower level of governments, which are responsible for over 90 percent of public expenditures. Given that key government functions (social policy, subsidies, education, etc), are performed at sub-national level, timely decision making on BiH Institutions revenues from indirect taxes is important in enabling timely implementation of their respective budgets.